Ultrastructural Studies of Platelet Aggregates From Human Subjects Receiving Clopidogrel and From a Patient With an Inherited Defect of an ADP-Dependent Pathway of Platelet Activation - Humbert, Michel; Nurden, Paquita; Bihour, Claude; Pasquet, Jean-Max; Winckler, Joelle; Heilmann, Eric; Savi, Pierre; Herbert, Jean-Marc; Kunicki, Thomas J.; Nurden, Alan T. (Arteriosclerosis, thrombosis, and vascular biology, 1996)
Our study investigated the effect of the antithrombotic drug clopidogrel (75 mg/d for 7 days) on the ultrastructure of platelet aggregates induced by ADP or 2-methylthio-ADP (2-MeS-ADP) in citrated platelet-rich plasma and examined the activation state of the GP IIb/IIIa complexes. Results were compared with those obtained for patient M.L., who has a congenital disorder characterized by a reduced and reversible platelet response to ADP. When untreated normal platelets were stimulated with high-dose ADP, electron microscopy revealed large and stable aggregates often surrounded by a layer of what appeared to be degranulated platelets. The reversible aggregates of platelets from subjects receiving clopidogrel or from patient M.L. did not show this layer. Electron microscopy showed that in both situations, the aggregates were composed of loosely bound platelets with few contact points. Immunogold labeling of ultrathin sections of Lowicryl-embedded aggregates formed by ADP or 2-MeS-ADP showed a much decreased platelet surface staining by (1) a polyclonal anti-fibrinogen antibody and (2) AP-6, a murine anti-ligand-induced binding site monoclonal antibody specific for GP IIb/IIIa complexes occupied with fibrinogen. Similar findings were seen after disaggregation, when many single platelets were present that showed no signs of secretion. Flow cytometry confirmed that the number of ligand-occupied GP IIb/IIIa complexes was much lower on platelets stimulated with ADP or 2-MeS-ADP after clopidogrel treatment. As expected from previous studies, ADP-induced platelet shape change and Calcium+ influx were unaffected by clopidogrel. These results agree with the hypothesis that platelet activation by ADP is biphasic and highlight a receptor-induced activation pathway affected by clopidogrel (or congenitally impaired in patient M.L.) that is necessary for the full activation of GP IIb/IIIa and the formation of stable macroaggregates. (Arterioscler Thromb Vasc Biol. 1996;16:1532-1543.)